Regional Own-Source Revenue, Regional Innovation, and Poverty Depth: The Mediating Role of Regional Development in Indonesia - Yass Andria; Dyah Poespita Ernawati (Department of Public Administration, 2026)
This study examines the effects of Regional Own-Source Revenue (PAD) and the Regional Innovation Index (RII) on the Regional Development Index (IMD) and their implications for the Poverty Gap Index (IKK) across 34 Indonesian provinces during the 2018–2024 period. Although fiscal decentralization has expanded the role of local governments in development financing, regional disparities in poverty depth remain persistent, particularly between western and eastern Indonesia. This study addresses this issue by developing a mediation-based panel data model that integrates fiscal capacity, government innovation, regional development performance, and delayed fiscal transmission. Using a balanced panel of 238 province-year observations, the analysis applies a Fixed Effect Model with robust standard errors, supported by panel specification tests, classical assumption diagnostics, mediation testing, and a one-period lag structure for PAD. The results show that PAD and RII have positive and significant effects on IMD, indicating that fiscal capacity and regional innovation contribute to stronger development performance. PAD, RII, and IMD also have negative and significant effects on IKK, confirming that fiscal resources, innovation capacity, and development outcomes are associated with lower poverty depth. The lagged PAD variable produces a stronger negative effect than current PAD, suggesting that local fiscal resources require at least one budget cycle before generating measurable welfare impacts. Mediation analysis confirms that IMD partially mediates the effects of PAD and RII on IKK, these findings imply that poverty-depth reduction requires not only stronger local revenue and innovation, but also effective conversion of fiscal and institutional capacity into inclusive regional development. The study contributes to fiscal decentralization and public sector innovation literature by highlighting the mediating role of development performance and the delayed nature of fiscal impacts on poverty depth.